2017
DOI: 10.1590/s0004-2803.2017v54n1-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyspeptic symptoms and heartburn of adults in Belo Horizonte, Brazil

Abstract: -Background -Medical literature has shown dyspepsia and heartburn related symptoms occur among 15% to 40% of the population. These symptoms can occur at any age and are more prevalent in women. Objective -Investigate the prevalence of dyspeptic symptoms and heartburn among individuals over 18. Methods -Individuals over 18 were randomly selected in public venues in Belo Horizonte/MG to participate. A standardized questionnaire that included questions related to social demographic characteristics, eating habits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
8
0
3
Order By: Relevance
“…Also, it was found that alcohol intake is related to dyspepsia, which is consistent with the findings in the article made by Almeida et al (1) . We consider that it is necessary to describe other risk factors for the development of dyspepsia, such as: NSAIDs consumption and Helicobacter pylori infection; since both are also important for the development of this pathology (3) , so we believe that it would be necessary to perform a Latin American study in collaboration with all the countries of the region to obtain accurate data of this important and prevalent pathology.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Also, it was found that alcohol intake is related to dyspepsia, which is consistent with the findings in the article made by Almeida et al (1) . We consider that it is necessary to describe other risk factors for the development of dyspepsia, such as: NSAIDs consumption and Helicobacter pylori infection; since both are also important for the development of this pathology (3) , so we believe that it would be necessary to perform a Latin American study in collaboration with all the countries of the region to obtain accurate data of this important and prevalent pathology.…”
supporting
confidence: 91%
“…
We have read with interest the article entitled: "Prevalence of dyspeptic symptoms and heartburn of adults in Belo Horizonte, Brazil" (1) . We would like to emphasize the importance of this article due to the little number of articles written in Latin America compared to those existing in other parts of the world.

The systematic review on global prevalence of dyspepsia by Ford et al 2014, shows a prevalence of 15%-19.9% for Brazil, which is not consistent with the results of Almeida et al This study also shows a 35% higher prevalence in Perú, and 37.7% for South America.

…”
mentioning
confidence: 99%
“…A study conducted in the southeast region of Brazil on patients with dyspepsia showed that epigastric pain was reported in 10%, post-prandial plenitude in 6.7%, and heartburn in 52.8% of patients. 18 In the United States, research involving patients with dyspepsia showed a prevalence of 51% for epigastric pain and 47% for post-prandial discomfort. The prevalence of heartburn was approximately 35.3% among the patients who had this symptom at least once a month, 19 which agrees with our study's data.…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequency of digestive symptoms in women was also observed in other studies. 18 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…21,23 In Brazil it may vary from 44% to 68,6%. 24 When addressed endoscopy? According to the American College of Gastroenterology guidelines, dyspeptic patients over 55 or with alarm factors: bleeding, anemia, unexplained weight loss (more than 10% of body mass), progressive dysphagia, odynophagia, persistent vomiting, family history gastrointestinal cancer, previous history of esophageal malignancy, peptic ulcer, lymphadenopathy or abdominal mass, should be promptly referred for upper gastrointestinal endoscopy to rule out the possibility of peptic ulcer disease, neoplasms and other rare gastrointestinal diseases.…”
Section: Introductionmentioning
confidence: 99%